2014
DOI: 10.1073/pnas.1321574111
|View full text |Cite
|
Sign up to set email alerts
|

DA-Raf–dependent inhibition of the Ras-ERK signaling pathway in type 2 alveolar epithelial cells controls alveolar formation

Abstract: Alveolar formation is coupled to the spatiotemporally regulated differentiation of alveolar myofibroblasts (AMYFs), which contribute to the morphological changes of interalveolar walls. Although the Ras-ERK signaling pathway is one of the key regulators for alveolar formation in developing lungs, the intrinsic molecular and cellular mechanisms underlying its role remain largely unknown. By analyzing the Ras-ERK signaling pathway during postnatal development of lungs, we have identified a critical role of DA-Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…The time course of the postnatal development of lipofibroblasts was studied in various rodent species showing first a postnatal increase and subsequently a decline in the adult lung (23). Recent studies, however, have also highlighted an important role of myofibroblasts during postnatal development of the mouse lung (56). The stereological data on the mouse and the rat lung provided in the present study indicate that the postnatal development of the lipofibroblasts is not identical in these two species, but the overall time course as described by Kaplan et al (23) is confirmed by our data.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The time course of the postnatal development of lipofibroblasts was studied in various rodent species showing first a postnatal increase and subsequently a decline in the adult lung (23). Recent studies, however, have also highlighted an important role of myofibroblasts during postnatal development of the mouse lung (56). The stereological data on the mouse and the rat lung provided in the present study indicate that the postnatal development of the lipofibroblasts is not identical in these two species, but the overall time course as described by Kaplan et al (23) is confirmed by our data.…”
Section: Discussionsupporting
confidence: 87%
“…The ability to store retinoic acid within the lipid bodies as well as the crucial role of retinoic acid for lung development has established an important role for this cell type in development of the normal rat lung (7,47). Besides lipofibroblasts, myofibroblasts have also been attributed a significant involvement in normal lung development (56). In addition, exogenous application of retinoic acid to elastase-induced emphysematous rat lungs has been shown to reverse the emphysematous alterations at least in part (27).…”
mentioning
confidence: 99%
“…There is, however, correlative data in an array of tissues suggesting that TIMP4 restricts ECM proteolysis in the developing lung [63], female reproductive tract [64], eyes [65], and transplanted tissues [66].…”
Section: Timp4 Direct Inhibition Of Ecm Proteolysis By Timp4mentioning
confidence: 99%
“…The airways evolve from tubular to saccular by transforming the epithelium from a cuboidal to a mosaic structure with type I and II cells, and associating capillaries with the base of the epithelium. In the final step, alveoli are formed by lifting septa with a free edge from the saccular walls, thus forming alveolar ducts surrounded by a sleeve of densely packed alveoli (27)(28)(29)(30)(31).…”
Section: The Complex Substrate Of the Alveolar Septamentioning
confidence: 99%